EFFECT OF RED GINGER EXTRACT (Zingiber officinale Var Rubrum) ON CHEMICAL AND ORGANOLEPTICS QUALITY OF AMBON CURUP BANANA WET “SALE” - Wuri Marsigit; Laili Susanti; Lia Marzalena (Jurnal Agroindustri, 2019)
ABSTRACTQuality improvement  of sale banana ambon curup was necessary to increase chemical and organoleptics quality and consumer preference. The  purpose  of  this  study  was  to  determine  the  effect  of  variations  in  theconcentration   of   red   ginger   juice   and   the   length   of   immersion   on  chemical   quality, microbiology and organoleptic wet sale of banana ambon curup. By using (RAL) 2 factorial randomized design, the concentration of red ginger juice was 5%, 10% and 15% with a time of immersion for 20 and 10 minutes. The analytical method used was ANOVA. The results of the study found that sucrose levels were 37.56% to 57.54 %, the water content was 36.66% and 38.33%, ash content was 1.47 % to 1.87 %.  The  panelists  preferred  the  average  value  of  the  whole (texture, aroma, and tate)  was  found  in  the  P1T1 sample  with  a  treatment  of  red  ginger  concentration  of  0.05%  and  immersion  time  for  10 minut